Integrating electronic healthcare records of armed forces personnel: Developing a framework for evaluating health outcomes in England, Scotland and Wales. (May 2018) - Leightley, Daniel; Chui, Zoe; Jones, Margaret; Landau, Sabine; McCrone, Paul; Hayes, Richard D.; Wessely, Simon; Fear, Nicola T.; Goodwin, Laura
Highlights: A framework which integration national Electronic Healthcare Record datasets from England, Scotland and Wales is proposed. Variable similarity is used to develop a schema which allows for variables to be linked and combined across the nations. Evaluation of integration shows that it is possibly to perform data linkage across the nations. Abstract: Background: Electronic Healthcare Records (EHRs) are created to capture summaries of care and contact made to healthcare services. EHRs offer a means to analyse admissions to hospitals for epidemiological research. In the United Kingdom (UK), England, Scotland and Wales maintain separate data stores, which are administered and managed exclusively by devolved Government. This independence results in harmonisation challenges, not least lack of uniformity, making it difficult to evaluate care, diagnoses and treatment across the UK. To overcome this lack of uniformity, it is important to develop methods to integrate EHRs to provide a multi-nation dataset of health. Objective: To develop and describe a method which integrates the EHRs of Armed Forces personnel in England, Scotland and Wales based on variable commonality to produce a multi-nation dataset of secondary health care. Methods: An Armed Forces cohort was used to extract and integrate three EHR datasets, using commonality as the linkage point. This was achieved by evaluating and combining variables which shared the same characteristics. EHRs representing Accident and Emergency (A&E), Admitted Patient Care (APC) and Outpatient care were combined to create a patient-level history spanning three nations. Patient-level EHRs were examined to ascertain admission differences, common diagnoses and record completeness. Results: A total of 6, 336 Armed Forces personnel were matched, of which 5, 460 personnel had 7, 510 A&E visits, 9, 316 APC episodes and 45, 005 Outpatient appointments. We observed full completeness for diagnoses in APC, whereas Outpatient admissions were sparsely coded; with 88% of diagnoses coded as " Unknown/unspecified cause of morbidity ". In addition, A&E records were sporadically coded; we found five coding systems for identifying reason for admission. Conclusion: At present, EHRs are designed to monitor the cost of treatment, enable administrative oversight, and are not currently suited to epidemiological research. However, only small changes may be needed to take advantage of what should be a highly cost-effective means of delivering important research for the benefit of the NHS.